Mitochondrial genome sequence of the protist Ancyromonas sigmoides Kent, 1881 (Ancyromonadida) from the Sugluk Inlet, Hudson Strait, Nunavik, Québec - Gastineau, Romain; Harðardóttir, Sara; Guilmette, Caroline; Lemieux, Claude; Turmel, Monique; Otis, Christian; Boyle, Brian; Levesque, Roger C.; Gauthier, Jeff; Potvin, Marianne; Lovejoy, Connie (Frontiers in Microbiology, 2023)
Introduction There is little information on evolutionarily ancient eukaryotes, which are often referred to as basal eukaryotes, in Arctic waters. Despite earlier studies being conducted in the Russian White Sea, only few have been reported. Methods Following a shotgun sequence survey of diatom cultures from Sugluk Inlet off the Hudson Strait in Northern Québec, we obtained the complete mitochondrial genome and the operon of nuclear ribosomal RNA genes from a strain that matches that of Ancyromonas sigmoides (Kent, 1881). Results The sequence of the mitogenome retrieved was 41,889 bp in length and encoded 38 protein-coding genes, 5 non-conserved open-reading frames, and 2 rRNA and 24 tRNA genes. The mitogenome has retained sdh2 and sdh3, two genes of the succinate dehydrogenase complex, which are sometimes found among basal eukaryotes but seemingly missing among the Malawimonadidae, a lineage sister to Ancyromonadida in some phylogenies. The phylogeny inferred from the 18S rRNA gene associated A. sigmoides from Sugluk Inlet with several other strains originating from the Arctic. The study also unveiled the presence of a metagenomic sequence ascribed to bacteria in GenBank, but it was clearly a mitochondrial genome with a gene content highly similar to that of A. sigmoides, including the non-conserved open-reading frames. Discussion After re-annotation, a phylogeny was inferred from mitochondrial protein sequences, and it strongly associated A. sigmoides with the misidentified organism, with the two being possibly conspecific or sibling species as they are more similar to one another than to species of the genus Malawimonas. Overall our phylogeny showed that the ice associated ancryomonads were clearly distinct from more southerly strains.